Influence of various pollutants to the environment on metabolic status laboratory animals organism - Shorin, S.S.; Mashzhan, A.S. (KSU Publ., 2018)
This article presents the results of an experimental study of dust containing a complex microconcentrations metals. Quantitative characteristics carcinogenic risk in inhalation and oral intake of chemical compounds have been established. The results of complex ecological studies on the evaluation unfavorable environmental factors, the carcinogenic risk of cancer development among the population living in the zone a dysfunctional region, specifies the features ecological and hygienic situation caused by chemical contamination of some natural environments (air, water, snow, soil). The role of low metal concentrations in the dust composition on the metabolic processes in the body has been experimentally established, the dose-dependent changes have been determined, that the trigger mechanism toxicity of chemical compounds is the inefficiency the cellular mechanisms in the splitting corpuscular microparticles of dust penetrating into the blood stream, provoking increased oxidative stress in the internal organs.
Қоршаған ортаның əртүрлі ластағыш заттарының зертханалық жануарлар ағзасының метаболикалық күйіне əсері
Влияние различных поллютантов окружающей среды на метаболический статус организма лабораторных животных
Keywords: environment, dust, experimental animals, chemical pollutants, toxicity, biological equivalent, maximum permissible concentration, biosphere, the soil, cytomorphological index